2021
DOI: 10.1088/2043-6254/abde41
|View full text |Cite
|
Sign up to set email alerts
|

Plant extract assisted synthesis of reduced graphene oxide sheet and the photocatalytic performances on cationic and anionic dyes to decontaminate wastewater

Abstract: Green synthesis of reduced graphene oxide (RGO) has gained momentum over chemical methods due to its environmental compatibility. The present study deals with the green synthesis of the RGO sheet using the bark extract of Alstonia scholaris by the simple heating method in less time duration. Different characterizations such as x-ray diffraction (XRD), ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy confirm the formation of RGO and the transmission electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, the small shoulder of GO at 335 nm disappeared in rGO samples. A similar observation is reported using other plant extracts (Ghosh et al 2021). Ding et al (2011) mentioned the red shift of the absorption band at 230 to 260 nm and the disappearance of the 300-nm band as an indication for the successful green synthesis of rGO nanosheets.…”
Section: Characterizationsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, the small shoulder of GO at 335 nm disappeared in rGO samples. A similar observation is reported using other plant extracts (Ghosh et al 2021). Ding et al (2011) mentioned the red shift of the absorption band at 230 to 260 nm and the disappearance of the 300-nm band as an indication for the successful green synthesis of rGO nanosheets.…”
Section: Characterizationsupporting
confidence: 81%
“…CoTPP (tetramethoxyphenylporphyrin)/rGO/ MWCNTs (multiwalled carbon nanotubes) nanocomposite that was prepared by Kiran et al (2020) resulted in 50% degradation of 5 ppm MB in 70 min. Ghosh et al (2021) showed that rGO, prepared by the bark extract of Alstonia scholaris, can degrade 12 ppm MB with 94.67% in 210 min. Consequently, the synthesized rGO possesses well efficiency in line with other phytosynthesized rGOs so it is thought to be a good catalyst for catalytic degradation of MB and other hazardous organic pollutants in wastewater.…”
Section: Catalytic Degradation Of Methylene Blue (Mb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption capacity (q max ) of rGO synthesized from Citrus hystrix peel extract on MB was determined to be 276.06 mg/g at room temperature [93]. Ghosh et al [97] reported the photocatalytic activity of rGO synthesis using the bark extract of Alstonia scholaris (with a duration of three hours) toward MB and methyl orange (MO). It has been demonstrated that MB degrades at a rate of 95.29%, whereas MO degrades at a rate of only 6%.…”
Section: Photocatalytic Degradationmentioning
confidence: 99%
“…The adsorption capacity (qmax) of synthesis rGO from Citrus hystrix peel extract on MB was determined to be 276.06 mg/g at room temperature [92]. Ghosh et al [96] reported the photocatalytic activity of rGO synthesis using the bark extract of Alstonia scholaris (time duration 3 hour) towards MB and methyl orange (MO). It has been demonstrated that MB degrades at a rate of 95.29 %, whereas MO degrades at a rate of only 6 %.…”
Section: Photocatalytic Degradationmentioning
confidence: 99%